Nurse manager's guide to budgeting & finance - Rundio, Al; Sigma Theta Tau International (Indianapolis : Sigma, 2022)
Updated to include details about key legislation that affects budgeting, The Nurse Manager's Guide to Budgeting and Finance, 3rd Edition, provides practical tools, tips, and strategies for running a unit that were not taught in nursing school.
Front cover -- Back cover -- Endorsements -- Title page -- Copyright page -- Dedication -- Acknowledgments -- About the author -- Table of contents -- Foreword -- Introduction -- Chapter 1. Budgeting for the nurse manager -- Chapter 2. Healthcare reimbursement -- Chapter 3. Budget types -- Chapter 4. Budget development -- Chapter 5. Operating budgets -- Chapter 6. Capital budgets -- Chapter 7. Budget variances -- Chapter 8. Budget reports -- Chapter 9. Healthcare reform and the Affordable Care Act -- Chapter 10. Governing boards of healthcare organizations and specialty nursing organizations -- Chapter 11. Improving quality and safety to increase reimbursement -- Chapter 12. Conclusions -- Index.
Includes bibliographical references and index.
Print version record.
WorldCat record variable field(s) change: 050
Keywords: Nursing services -- Business management; Nursing services -- Finance; Nursing services -- Administration; Nursing, Supervisory; Services infirmiers -- Finances; Services infirmiers -- Administration; Nursing services -- Business management; Nursing services -- Finance; Nursing services -- Administration; Electronic books; Electronic books; Electronic books